How often is a work-up for Legionella pursued in patients with pneumonia? A retrospective study - Mermel Leonard A; Dupont Irene; Hollenbeck Brian (BMC Infectious Diseases, 2011)
Abstract Background It is unclear how often patients with pneumonia are assessed for Legionella in endemic areas. Additionally, the sensitivity of the IDSA/ATS criteria for recommended Legionella testing is undefined. Methods We performed a single-center, retrospective study of patients diagnosed with Legionella pneumonia at our hospital to determine: 1) how often Legionella diagnostic testing is obtained on patients with pneumonia at the time of hospitalization or when pneumonia developed during hospitalization; and 2) how often patient's with Legionella pneumonia met at least one of the five criteria in the IDSA/ATS guidelines recommending a work-up for Legionella. Patients with Legionella pneumonia were identified using an infection control software program. Medical records of these patients were then reviewed. Results Thirty-five percent of patients with a discharge diagnosis of pneumonia had Legionella urine antigen testing and/or a Legionella culture performed. Forty-four percent of patients who had a bronchoscopic specimen sent for microbiologic testing had a Legionella culture performed on the bronchoscopic specimen and/or Legionella urine antigen testing. Of 37 adult patients with Legionella pneumonia, 22 (59%) met the IDSA-ATS criteria recommending Legionella testing. Conclusion Following current recommendations for Legionella testing missed 41% of Legionella cases in adults in our single-center study. A work-up for Legionella (i.e., urine antigen test and/or culture) was performed in less than half of patients who have a bronchoscopic specimen sent for microbiologic testing.